Organizational-technological and information-telecommunication aspects of creating an information-educational environment of a higher educational institution - Заболотня, Ю. В. (Pedagogy of Higher and Secondary Education, 2021)
The article is devoted to the organizational-technological and informational-telecommunication aspects of creation of the informational-educational surroundings of a higher educational institution.